Manajemen Sarana dan Prasarana Olahraga dalam Upaya Meningkatkan Prestasi Non Akademik Siswa - Supriatna, Acep; Dahtiar, Dadan; Soro, Suharyanto; Mardiana, Dinny (Civiliza Publishing, Indonesia., 2025)
This study aims to describe in depth how the management of sports facilities and infrastructure contributes positively to the improvement of non-academic achievement of students. The focus of the research departs from the problem of limited school sports facilities and their management that is not optimal, so that students have not received adequate environmental support to develop their potential and achievements in the field of sports. Using the POAC (Planning, Organizing, Actuating, Controlling) theoretical framework, this study traces how the process of planning, organizing, implementing, and supervising sports infrastructure facilities is carried out by schools. This research uses a qualitative paradigm with data collection methods in the form of observation, in-depth interviews, and documentation studies. Respondents in this study included school principals, PJOK teachers, infrastructure management staff, and other related parties. All data were analyzed through a systematic process of reduction, presentation, and conclusion drawn. The results of the study show that sports infrastructure planning has been carried out, but it has not fully referred to the applicable educational facility standards. The organization already has a basic structure, but its implementation has not been optimally carried out due to limited resources. At the implementation level, the use of infrastructure in both PJOK and extracurricular learning is not optimal due to the limited availability of tools and training spaces. Meanwhile, supervision is carried out informally and has not been supported by a structured evaluation mechanism. This study emphasizes that the management of well-planned, organized, and supervised sports facilities and infrastructure is a strategic factor in improving students' non-academic achievement. Strengthening planning, improving coordination, optimizing the use of facilities, and continuous supervision are steps that need to be taken by schools.